2005
DOI: 10.1007/s10120-005-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastric choriocarcinoma: two case reports and a pooled analysis of 53 cases

Abstract: rameters of PGCs were described in some of these reports, most of the conclusions were unreliable because of the small number of PGC cases analyzed.In the present study, we conducted a pooled analysis of 53 PGC cases, including 2 patients treated at the National Cancer Center Hospital East (NCCHE), to clarify the tumor characteristics and prognostic parameters of patients with PGC. Case reports Case 1A 74-year-old man complaining of loss of appetite and loss of body weight, for 9 months, visited the NCCHE. Lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
96
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(117 citation statements)
references
References 14 publications
(7 reference statements)
1
96
1
4
Order By: Relevance
“…Most cases show metastasis at the time of presentation and the most common sites of metastasis are lymph nodes followed by liver, peritoneum and lungs. In our case, there was no evidence of metastasis at presentation [6].…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Most cases show metastasis at the time of presentation and the most common sites of metastasis are lymph nodes followed by liver, peritoneum and lungs. In our case, there was no evidence of metastasis at presentation [6].…”
Section: Discussioncontrasting
confidence: 47%
“…Kobayashi et al performed a pooled analysis of 53 patients reported in the literature so far with PGC and described a male to female ratio of 2.3:1 with a median age at presentation of 63 years. Lower third of the stomach was found to be the most frequent location of PGC [6].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It often arises in the uterus in association with pregnancy, and its most common extragonadal sites are the mediastinum, ovary and testis [1] . Primary gastric choriocarcinoma (PGC) is a rare neoplasm that constitutes less than 1% of all gastric cancers [2] . It was first described by Davidsohn in 1905 and more than 140 cases have been reported in the international medical literature.…”
Section: Introductionmentioning
confidence: 99%
“…Primary carcinoma of the stomach is almost always adenocarcinoma or signet ring cell carcinoma and there have been few reports of choriocarcinoma [1][2][3][4][5] or neuroendocrine cell carcinoma [6][7][8][9] . We report a patient with adenocarcinoma of the stomach combined with choriocarcinoma and neuroendocrine cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%